A Multistandard Frequency Offset Synchronization Scheme for 802.11n, 802.16d, LTE, and DVB-T/H Systems. (8th February 2010) - González-Bayón, Javier; Carreras, Carlos; Edfors, Ove
Abstract : Carrier frequency offset (CFO) synchronization is a crucial issue in the implementation of orthogonal frequency division multiplexing (OFDM) systems. Since current technology tends to implement different standards in the same wireless device, a common frequency synchronization structure is desirable. Knowledge of the physical frame and performance and cost system requirements are needed to choose the most suitable scheme. This paper analyzes the performance and FPGA resource requirements of several data-aided (DA) and decision-directed (DD) schemes for four wireless standards: 802.11n, 802.16d, LTE, and DVB-T/H. Performance results of the different methods are shown as BER plots and their resource requirements are evaluated in terms of the number of computations and operators that are needed for each scheme. As a result, a common architecture for the four standards is proposed. It improves the overall performance of the best of the schemes when the four standards are considered while reducing the required resources by 50%.